The imagined community of sexually liberal citizens: educational reforms since the 1970s. Issue 3 (4th May 2018) - Rothmüller, Barbara
ABSTRACT: Recent integration discourses in Europe locate problems of equality, gender, and sexuality among migrant youth. Educating and testing the values of future citizens is supposed to guarantee their conformity with 'western' and 'modern' values. By analyzing educational reform discourses in multicultural Luxembourg, the paper aims to challenge these contemporary narratives in two ways: (1) In a historical analysis, the paper traces conservative reform resistance in the case of sex education which is often overlooked due to the focus on migrants; (2) In placing sex education's reform legitimation and resistance within (a) broader educational reform discourses of inequality and citizenship and (b) contemporary narrations of the reforms and their taboos, the paper reconstructs how liberals and conservatives join an alliance over sexuality education of 'the Other'. The sociological–historical discourse analysis critically questions the ethnicization of sexuality by disclosing its homogenizing use to cover conservative resistance within the citizen's community.